The need of an updated culture of “occupational” atopic hand dermatitis in children at the time of COVID-19: From two cases report to an update culture of atopic dermatitis - Pecoraro, Luca; Chiaffoni, Giovanni; Piacentini, Giorgio; Pietrobelli, Angelo (Acta Biomedica Atenei Parmensis, 2022)
During the COVID-19 outbreak, handwashing emerged as an essential tool to prevent the spread of SARS-CoV-2 virus. It can put into practice using warm water and soap or, if not available, alcohol-based hand sanitizers (ABHS). Anyway, the use of warm water and soap is not always possible. On the contrary, ABHS are frequently used for their versatility, but can represent a risk factor for atopic dermatitis exacerbations in the pediatric age. At the same time, the Italian Ministry of Health established a school regulation, asking the students to periodically disinfect hands with sanitizing gel, or soap and water, especially before entering classrooms and laboratories, immediately after contact with everyday objects, after using the toilet, after throwing away the handkerchief and before and after eating. No rules have been personalized in this statement for children affected by atopic dermatitis attending the school. Based on this observation, we reported two case reports, involving children with a known diagnosis of atopic dermatitis, who attended our Pediatric Allergy Unit in Mantua, Italy. They experienced a worsening of symptoms related to AD on their hands in the last year for an intensive handwashing with ABHS before entering all classrooms and laboratories every day at school. Avoiding ABHS at school and washing their hands with a non-alcohol and additives soap and water solved their problem and brought their atopic dermatitis back to good control. So, it seems appropriate to consider ABHS as a “school trigger” and the low-controlled atopic dermatitis of these two patients as an “occupational dermatitis”. An adequate pediatric culture of atopic dermatitis at the time of COVID 19 is needed.